Fracture and Failure Analysis of Wheel Bolt on Main Landing Gear CN235 220M Aircraft - Dewa, Rando Tungga; Daffa Mandala Adinata; Ida Farida; Sovyan Aritonang; Hadi Wahyudi (Mechanical Engineering Department - Semarang State Polytechnic, 2025)
The wheel bolt of the CN235 220M aircraft is a type of fastener crucial for maintaining air pressure within the tire. It was discovered that this component fractured during operation. This study aims to conduct forensic analysis on the mechanism and causes of material failure through micro and macro morphological observations, chemical composition tests, microstructural analysis, and hardness testing on the fractured bolt. Micro-morphology results showed a crack tip in the initiation zone, which became a stress concentration point. Additionally, striations caused by cyclic loading were observed. EDS analysis revealed a high oxygen content in the initiation zone, indicating a corrosion-assisted crack. As cyclic loading continued, it gradually eroded the bolt's cross-sectional area until the material's fatigue led to final fracture.